2022
DOI: 10.3390/ijms23147784
|View full text |Cite
|
Sign up to set email alerts
|

Application of Lactic Acid Bacteria (LAB) in Sustainable Agriculture: Advantages and Limitations

Abstract: Lactic acid bacteria (LAB) are significant groups of probiotic organisms in fermented food and are generally considered safe. LAB regulate soil organic matter and the biochemical cycle, detoxify hazardous chemicals, and enhance plant health. They are found in decomposing plants, traditional fermented milk products, and normal human gastrointestinal and vaginal flora. Exploring LAB identified in unknown niches may lead to isolating unique species. However, their classification is quite complex, and they are ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 130 publications
0
56
0
3
Order By: Relevance
“…The maintenance of intracellular pH homeostasis is achieved through proton motive forces created by respiration around the cytoplasmic membrane, which works simultaneously with the extrusion of toxic Na+ ions from the cell while it takes in protons. The Na + /K + /H + antiporter, a major system of pH homeostasis, is encoded by the tetA(L) gene in B. subtilis [ 74 , 75 , 76 , 77 , 78 ]. At an elevated pH of about 8, it was reported that the tetA(L) gene was upregulated by 1.8–2.5 fold [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of intracellular pH homeostasis is achieved through proton motive forces created by respiration around the cytoplasmic membrane, which works simultaneously with the extrusion of toxic Na+ ions from the cell while it takes in protons. The Na + /K + /H + antiporter, a major system of pH homeostasis, is encoded by the tetA(L) gene in B. subtilis [ 74 , 75 , 76 , 77 , 78 ]. At an elevated pH of about 8, it was reported that the tetA(L) gene was upregulated by 1.8–2.5 fold [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…This metabolic pathway mainly occurs in lactic acid bacteria (LAB), such as those belonging to the Lactobacillus species of the class Bacilli. The LAB, apart from their use in the food industry, are also used in agricultural systems to improve soils, promote plant growth, and mitigate abiotic and biotic stresses, whilst also serving as biocontrol agents and can be used as biostimulants, in biofertilisers, and bioremediation processes [ 101 , 102 ]. Herein, Bacillus and unclassified Bacillales species were enriched mainly in the DC soils, corroborating the significant increase in lactic acid fermentation processes, and indicating a potential association with the runner bean crop.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of prokaryotes, the heterogeneous group of lactic acid bacteria (LAB) represents a promising reservoir of potential bio-based solutions for sustainable agriculture, also in terms of postharvest applications [ 134 , 135 ]. LAB generally have a long history of safe use in food fermentations and, also due to this characteristic, several LAB species are recognized as having facilitated paths in defining their safe use in food, according to the different legislative environments [ 136 , 137 ].…”
Section: Postharvest Strategies To Extend the Shelf-life Of Fruit And...mentioning
confidence: 99%